Inbreeding decreases promiscuity in Drosophila melanogaster females. Issue 2 (2nd April 2016) - Dolphin, K.E.; Carter, A.J.R.
Abstract : Polyandry and promiscuity by females are widespread phenomena in natural populations despite the costs associated with multiple matings. Previous studies using flour beetles ( Tribolium castaneum ) and field crickets ( Gryllus bimaculatus ) suggest that these behaviors are more common in inbred individuals, perhaps as a mechanism to ensure genetic diversity in the offspring produced or due to reduced choosiness. However, using Drosophila melanogaster, we observed the converse pattern; relatively inbred females were less promiscuous than relatively outbred ones both in terms of the number of males and the number of phenotypes of males chosen, and took longer to copulate which is consistent with increased choosiness. The effects of inbreeding on behavior may therefore be different across different species and may depend on tradeoffs that differ between species rather than follow a general rule.